Multi-objective optimization design of the ejector plate for rear-loader garbage trucks - Ding, Fu-sheng (Strojniški vestnik, 2025)
This work presents a multi-objective optimization design approach for the ejector plate, a critical component of rear-loading garbage trucks, with the goal of maintaining structural integrity while optimizing lightweight performance. A parametric finite element model of the ejector plate is developed with optimization objectives focused on minimizing mass, maximizing deformation limits, and reducing the maximum von Mises stress. Through sensitivity analysis, seven key variables are identified as constraints. A Box-Behnken design (BBD) is used to systematically design these parameters, and a Kriging surrogate model is created to approximate the objective function, with performance compared to response surface methodology (RSM). The Non-dominated Sorting Genetic Algorithm II (NSGA-II) is applied to derive the optimal solution, achieving a lightweight design meeting all structural requirements. The results show that the mass of the ejector plate of the rear-loading waste compactor can be reduced by 6.06 % through structural optimization, while meeting the strength and deformation criteria. This improvement not only enhances waste transportation efficiency, but also lowers production costs and enhances material utilization.
Keywords: ejector plate; garbage truck; iztisna plošča; Kriging; multi-objective optimization; NSGA-II; smetarsko vozilo; večkriterijska optimizacija